2003
DOI: 10.1007/s10123-003-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Innovative tools for detection of plant pathogenic viruses and bacteria

Abstract: Detection of harmful viruses and bacteria in plant material, vectors or natural reservoirs is essential to ensure safe and sustainable agriculture. The techniques available have evolved significantly in the last few years to achieve rapid and reliable detection of pathogens, extraction of the target from the sample being important for optimising detection. For viruses, sample preparation has been simplified by imprinting or squashing plant material or insect vectors onto membranes. To improve the sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
173
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(175 citation statements)
references
References 73 publications
0
173
0
2
Order By: Relevance
“…In addition, these tests require specific indicator plants for each pathogen (Roistacher, 1991;Durán et al, 1993), which must be combined with the technique of sequential polyacrylamide gel electrophoresis (sPAGE). The most recent method for the detection of pathogens is PCR real time; however, this technique is still quite expensive, which is the principal problem for implementing its routine use in laboratories (López et al, 2003), though for detecting viral diseases in citrus, the results have been shown to be fast and reliable (Rizza et al, 2009;Loconsole et al, 2010).…”
Section: Multiple Rt-pcrmentioning
confidence: 99%
“…In addition, these tests require specific indicator plants for each pathogen (Roistacher, 1991;Durán et al, 1993), which must be combined with the technique of sequential polyacrylamide gel electrophoresis (sPAGE). The most recent method for the detection of pathogens is PCR real time; however, this technique is still quite expensive, which is the principal problem for implementing its routine use in laboratories (López et al, 2003), though for detecting viral diseases in citrus, the results have been shown to be fast and reliable (Rizza et al, 2009;Loconsole et al, 2010).…”
Section: Multiple Rt-pcrmentioning
confidence: 99%
“…phaseolicola in bean seed extracts, Acidovorax avenae ssp. avenae in rice seeds (Schaad et al, 1995;López et al, 2003;Song et al, 2004).…”
Section: Bio-pcrmentioning
confidence: 99%
“…Polymerase chain reaction has been used successfully to detect a range of viruses including both DNA and RNA viruses (Chandler et al, 1998). However, detection of viral RNA by PCR requires reverse transcription (RT) of viral RNA prior to the reaction (Lopez et al, 2003). Rice viruses, except Rice tungro bacilliform virus (RTBV), are RNA viruses, and synthesis of cDNA of the viral genome by reverse transcription (RT) is necessary before the target RNA sequence is amplified (Uehara-Ichiki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%